The Domestic Political Economy of China’s Foreign Aid - Mueller, Joris (The Review of Economics and Statistics, 2025)
Abstract I study how domestic political considerations influence the foreign policy choices of autocratic regimes, by analyzing China’s foreign aid. First, using contractor-level data, I document how the regime uses foreign aid projects to help maintain domestic stability: aid projects are awarded to state-owned firms in Chinese prefectures hit by social unrest, increasing employment and future political stability. Second, I find that this strategy to manage domestic unrest affects the global allocation of Chinese aid, since state-owned firms pursue projects in countries where they have prior connections.